Analgesic efficacy of pre-operative tramadol in combination with acepromazine in cats undergoing ovariohysterectomy - Basiri, Bita; Chen, Hui Cheng; Rahman, Nor Alimah (Faculty of Veterinary Science, University of Agriculture, Faisalabad, 2014)
In a randomized blind trial, cats undergoing ovariohysterectomy were premedicated subcutaneously with 4 mg/kg tramadol and 0.1 mg/kg acepromazine (Group AT4); 2 mg/kg tramadol and 0.1 mg/kg acepromazine (Group AT2); or 0.1 mg/kg acepromazine (Group ACE). Composite pain scores (CPS), and mechanical thresholds at metatarsal pad (MTp) and surgical site (MTs) were determined at -0.5, 0.5, 2.5, 3.5, 4.5, 6.5, 8.5, 10.5, 12.5, 12 and 48 hours after pre-medication. Post-operatively, CPS was the highest in ACE and all cats required rescue analgesia. None of the cats in AT4 or AT2 needed rescue analgesia. Group AT4 has lower CPS and higher MTp compared to AT2. Decrement of MTs tended to be the least in AT4. This study shows that tramadol at 4 mg/kg provided more profound and longer duration of analgesic effect than 2 mg/kg, when combined with acepromazine for premedication in cats.